Bulgaria Money and Banking : the Basics on Currency and Money in Bulgaria. - Press, World Trade (World Trade Press, 2010)
Money is a primary need when you're on the road and has the potential to cause major stress. Get the upper hand with this informative report on currency, traveler's checks, money wiring, ATMs, banks, and credit cards in Bulgaria.